IMPACT OF BORDER DISPUTES ON INDIGENOUS COMMUNITIES IN NORTH EAST INDIA (International Journal of Food and Nutritional Sciences, 2022)
This paper delves into the profound impact of border disputes on indigenouscommunities in North East India, shedding light on the multifaceted consequences thatthese conflicts have on the lives of the region's original inhabitants